Implementasi Psychological First Aid Berbasis Komunitas melalui Aktivitas Kelompok Terapeutik dalam Mendukung Pemulihan Kesejahteraan Psikologis Anak Pascabencana Banjir - Hendri, Hendri; Safrilsyah, Safrilsyah; Azhari, Azhari; Mohd Yusof, Muhammad Hasmimie Bin (Jurnal Bimbingan dan Konseling Islam, 2026)
Children are among the most vulnerable groups affected by hydrometeorological disasters because of their limited psychological coping capacity. Disaster-related traumatic experiences may cause emotional distress, impaired social interaction, and disrupted psychosocial functioning. This study explored the implementation of community-based Psychological First Aid (PFA) through therapeutic group activities to support the psychological well-being of children affected by flooding in Gampong Pulo Lhok, Ulim District, Pidie Jaya Regency, Indonesia. A qualitative study with a thematic design was conducted involving 60 elementary school-aged children (7-12 years) selected through purposive sampling. Data were collected using participant observation, semi-structured interviews, field notes, and documentation and analyzed using Braun and Clarke thematic analysis. Four major themes emerged: (1) reduction of psychological distress, (2) enhancement of positive emotional expression, (3) restoration of social interaction and psychosocial functioning, and (4) emergence of hope and optimism. Community-based PFA contributed to improving emotional regulation, strengthening peer interaction, fostering a sense of safety, and facilitating children's adaptive expression of traumatic experiences. From the perspective of Islamic Guidance and Counseling, these findings indicate that community-based PFA can be integrated with Islamic values, including rahmah (compassion), ta'awun (mutual assistance), and raja' (hope), to provide a holistic psychosocial support model for children affected by disasters. This study contributes to the development of community-based crisis counseling practices within the framework of Islamic Guidance and Counseling.